Achieving High‐Power and Dendrite‐Free Lithium Metal Anodes via Interfacial Ion‐Transport‐Rectifying Pump. Issue 12 (2nd February 2023) - Feng, Yang; Zhong, Beidou; Zhang, Ruochen; Peng, Maoyu; Hu, Zhe; Wu, Zhonghan; Deng, Nanping; Zhang, Wang; Zhang, Kai
Abstract: Metallic lithium is a fascinating anode for the next‐generation energy‐dense rechargeable batteries owing to the highest theoretical specific capacity and lowest electrochemical potential. Nevertheless, sluggish desolvation kinetics and notorious dendritic growth hinder its electrochemical performance and safe operation. Herein, an interlamellar Li + conductor of Ag‐montmorillonite (AMMT) is proposed as an interfacial ion‐transport‐rectifying pump to induce the rapid and reversible plating/stripping of Li metal. Joint experimental and computational analyses reveal that the AMMT pump with negative charge layers and inherent channels can lower the desolvation energy and boost Li + transport. The resultant Li anode is endowed with a low nucleation barrier (22.2 mV) and dendrite‐free features, leading to high plating/stripping density (8 mA cm ‐2 ) and long lifespan (2500 h). Moreover, the corresponding Li||LiFePO4 batteries achieve a steady circulation (500 cycles@82%, 1 C) with a low N/P ratio. This strategy offers a fresh insight into constructing robust multifunctional electrolyte/Li anode interface for Li metal batteries. Abstract : An interfacial ion‐transport‐rectifying pump (composed of negative charge interfaces, ion channels, and lithiophilic sites) is strategically designed for tackling the chronic issue of dendritic growth of lithium. The synergetic interactions of the pump decrease the desolvation energy barrier and facilitate fast and homogenized Li‐ion flux, which results in smooth and stabilized Li growth and outstanding cycling stability.